The impact of a student's study time journal as a lesson and learning study. Issue 1 (3rd January 2017) - Tetteh, Godson A.
Abstract : Purpose: The purpose of this paper is to investigate the relationship between a student's study time and the learning outcome from a perspective that will correspond to Bloom's (1956) taxonomy and how teaching can be developed using variation theory. Design/methodology/approach: The author designed a learning study using an experiment with three different classes of students. The experimental research question was "Does a student's study time (massed or distributed spacing) have an impact on the learning process?" Findings: Results indicated that students in the "strictly supervised study time" grouping improved on their learning outcomes more than those in the "not strictly supervised study time" equivalent and those in the control group. It is important for students to manage their own learning activities and follow a regular study routine to improve their learning outcomes. Research limitations/implications: This study used undergraduate students at a university in Ghana, and its findings may not necessarily be applicable to other populations. One other limitation was that the author did not control for the lecturer's expectations and how these may have influenced students' learning outcomes. Another potential limitation was that total quality management was the only subject area used for this study. Practical implications: The objective of the study was to use the motivated strategies for learning questionnaire (MSLQ) approach by Pintrich et al. (1991) to determine the relationship between a student's study time and the impact on their learning outcomes. The results imply that students must take more active roles in their learning by having regular study time. Originality/value: Currently, to the best of the author's knowledge, there are not many experiment-based research studies on a student's study time using the MSLQ approach by Pintrich et al. (1991). This study contributes to the existing literature by examining how a student's study time (massed or distributed spacing) has an impact on the learning outcome as a lesson and learning study.